2008
DOI: 10.1039/b712159h
|View full text |Cite
|
Sign up to set email alerts
|

Temperature influence on the energy of nonspecific and specific interactions taking place between 4-aminophthalimide (4-AP) and homogeneous solvents

Abstract: Temperature induced spectral shifts of the 4-aminophthalimide (4-AP) emission spectra have been measured and compared to the predictions of the McRae solvent induced shift theory (J. Phys. Chem., 1957, 61, 562-572). Three moderately polar chloroalkanes selected as nonspecifically interacting media, and six hydrogen accepting or/and electron pair donating solvents have been used as the media in which the temperature influence on 4-AP-solvent interactions has been studied in the range of 180-320 K. Using the ab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(44 citation statements)
references
References 30 publications
(46 reference statements)
6
37
1
Order By: Relevance
“…Additionally, Dn HB temperature dependence found for C153, using the same method as in Ref. [1], is quite similar to the one found for 4-AP in the same 1-chloroalkanes. This observation indicates some universality in the observed temperature-induced changes in hydrogen bond energy.…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…Additionally, Dn HB temperature dependence found for C153, using the same method as in Ref. [1], is quite similar to the one found for 4-AP in the same 1-chloroalkanes. This observation indicates some universality in the observed temperature-induced changes in hydrogen bond energy.…”
Section: Introductionsupporting
confidence: 81%
“…Thus, the study reported previously for 4-AP [1] and in this paper for C153, although for model systems, can give important information, useful in the interpretation of observations made in much more complex systems, and can be of practical importance. Although this paper does not lead to definitive conclusions, it brings a new contribution to the hitherto knowledge of the influence of temperature on intermolecular interactions.…”
Section: Introductionmentioning
confidence: 50%
See 3 more Smart Citations